Educational technology as an integrative complementary strategy in the training of students and professionals in the health area: Integrative review (Research, Society and Development, 2021)
This study aims to describe the bibliographic content available in the literature on the use of educational technologies as integrative complementary tools in the training of students and health professionals, with a view to supporting the promotion of health education and promoting viable and accessible alternatives in the development of educational methods in clinical cytology. The study comprised the first stage of theoretical development applied to the construction of Webtechnology, mediated from an integrative bibliographic review, observational and qualitative in nature, based on studies that reiterate themes about educational technologies as tools for the professional development in the health field. The results found mainly deal with the need to change the way of learning, based on the scope for adapting new means and technologies for the higher education system. According to the trends observed in the teaching environment, changes in the requirements of education and society have been widely discussed in the literature. Adherence to these technologies should expand the potential for generating knowledge, in addition to the development of clinical cytology students, revolutionizing the role of the professional and translating new changes in the practice of teaching in cytology.